Oleanane-type glycosides from Weigela x Styriaca and two cultivars of W. florida: "Minor black" and "Brigela". (August 2022) - Hobloss, Samir; Bruguière, Antoine; Champy-Tixier, Anne-Sophie; Miyamoto, Tomofumi; Tanaka, Chiaki; Dessertaine, Simon; Sautour, Marc; Lacaille-Dubois, Marie-Aleth; Mitaine-Offer, Anne-Claire
Abstract: Sixteen oleanane-type glycosides were extracted from three Weigela hybrids and cultivars: W. x Styriaca, W. florida "Minor black" and W. florida "Brigela", and four of them were previously undescribed ones: 3- O -β-D -xylopyranosyl-(1→4)-β-D -xylopyranosyl-(1→3)-α-L -rhamnopyranosyl-(1→2)-β-D -xylopyranosyloleanolic acid, 3- O -β-D -xylopyranosyl-(1→4)-β-D -xylopyranosyl-(1→3)-α-L -rhamnopyranosyl-(1→2)-α-L -arabinopyranosyloleanolic acid, 3- O -β-D -xylopyranosyl-(1→4)-β-D -xylopyranosyl-(1→4)-β-D -xylopyranosyl-(1→3)-α-L -rhamnopyranosyl-(1→2)-α-L -arabinopyranosyloleanolic acid, and 3- O -β-D -xylopyranosyl-(1→4)-β-D -xylopyranosyl-(1→4)-β-D -xylopyranosyl-(1→4)-β-D -xylopyranosyl-(1→3)-α-L -rhamnopyranosyl-(1→2)-α-L -arabinopyranosyloleanolic acid. Their full structural elucidation required extensive 1D and 2D NMR experiments, as well as mass spectrometry analysis. Six compounds among the known ones were in sufficient amount to be tested for their antifungal activity against Candida albicans, and their antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa . Graphical Abstract: ga1 Highlights: Sixteen saponins were isolated, among which four new. Their structures were elucidated by extensive spectroscopic analyses. The chemotaxonomy of the Weigela genus was discussed, based on the structure of the isolated glycosides. Five of the isolated compounds were tested against Candida albicans, Staphylococcus aureus and Pseudomonas aeruginosa .